Southeast Asian regionalisn and China's soft power strategy in global age1 - Rommel C. Banlaoi, (Penerbit UKM, 2010)
This article examines Southeast Asian regionalism amidst globalization in the context of China’s soft power strategy in the region. This article contends that its model of regionalism allows Southeast Asia to cope with the challenges of globalization and provides countries in the region a louder and collective voice when dealing with major powers like China. While there seems to be a convergence of Southeast Asian regionalism and China’s use of soft power, this article identifies some pitfalls that limit the luster of China’s soft power appeal in the region.